Structured Literature Analysis on Sustainability Report Disclosure in Public Sector Organizations - Arifai, Muhammad; Mariana, Mariana; Fahlevi, Heru; Indriani, Mirna; Darwanis, Darwanis (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study examines the adoption of sustainability reporting in Public Sector Organizations (PSOs), focusing on (1) stakeholder expectations, (2) implementation challenges, and (3) the impact on accountability and value creation. It also identifies existing gaps in sustainability reporting frameworks and provides strategic recommendations to enhance transparency and effectiveness in public sector sustainability disclosures.Methodology: A Structured Literature Review (SLR) was conducted on 97 articles from Scopus (1990–2024), selected using keywords such as "sustainability reporting," "public sector," "GRI framework," and "public sector organizations." Inclusion criteria ensured relevance to the public sector and methodological diversity. The articles were categorized by sustainability focus, country, research methods, and theoretical frameworks. This approach enabled the identification of research trends, key gaps, and best practices to support policy improvements in sustainability reporting.Findings: The review reveals that (1) research on sustainability reporting in PSOs is still limited and predominantly conducted in developed countries, (2) there is an increasing trend in sustainability reporting driven by demands for greater transparency and accountability, (3) major challenges include inconsistencies in reporting frameworks, varied stakeholder expectations, and difficulties integrating sustainability metrics, and (4) adoption is influenced by regulatory environments, political commitment, and resource availability. Although digital reporting tools are emerging, standardization and performance measurement issues remain unresolved.Conclusion: Despite progress, sustainability reporting in PSOs suffers from a lack of consistency, comparability, and stakeholder engagement. To improve credibility and effectiveness, harmonized standards, stronger regulatory oversight, and capacity-building initiatives are essential. Addressing these gaps will enhance accountability and foster long-term value creation in the public sector.